Search by committee - James Albrecht; Axel Anderson; Susan Vroman (Institute for the Study of Labor (IZA), 2007)
We consider the problem of sequential search when the decision to stop searching is made by a committee. We show that a symmetric stationary equilibrium exists and is unique given that the distribution of rewards is log concave. Committee members set a lower acceptance threshold than do single-agent searchers. In addition, mean preserving spreads in the distribution of rewards may lower each member's continuation value - an impossibility in the single-agent setting. If committee members are very patient or very impatient, expected search duration is lower than it would be for a single agent, but, for intermediate levels of patience, this comparison may be reversed. Holding the fraction of votes required to stop fixed, expected search duration rises with committee size on patient committees but falls with committee size on impatient committees. Finally, we consider the effect of varying the number of votes required to stop, holding committee size constant. We show that the welfare-maximizing vote threshold increases in the rate of patience and that there is a finite bound on patience such that unanimity is welfare maximizing.
Keywords: 330; Sequential search; voting; Suchtheorie; Gruppenentscheidung; Public Choice; Theorie